A general strength model for fiber bundle composites under transverse tension or interlaminar shear. (June 2019) - Li, Wen; Chen, Wei; Tang, Liqun; Jiang, Zhenyu; Huang, Peiyan
Abstract: Fiber bundle composites (FBCs), prepared by embedding a piece of fiber bundle in polymer matrix, can imitate the part in unidirectional FRP laminates which fails under transverse tension or interlaminar shear. However, there is a remarkable discrepancy between the results obtained in the tests of FBCs and corresponding standard tests of laminates. This paper explores the reasons for the observed gaps, which are found related with the more complex stress states along the fiber-bundle/polymer heterointerface in FBCs. Two strength models have been developed for the FBCs subjected to transverse tension and Iosipescu shear respectively, which can be further unified to a general form ( σ - 2 = δ 1 σ 1 - 2 + δ 2 σ 2 - 2 ). The proposed strength model shows good prediction capability in experimental verification using six groups of composite systems. This study lays a theoretical basis for assessment of the transverse tensile strength or interlaminar shear strength of unidirectional FRP laminates through the simple tests of FBCs.